The Provision of Health Care by Family Physicians in Taiwan as Illustrated With Population Pyramids. - Wang, Yi-Jen; Liu, Hao-Yen; Chen, Tzeng-Ji; Hwang, Shinn-Jang; Chou, Li-Fang; Lin, Ming-Hwai (Inquiry (00469580), 2019)
Family physicians serve as personal doctors for individuals and their families and also act as gatekeepers of the health care system. If no special status is accorded to family physicians, however, then the rates at which health care recipients utilize their service might be affected. In the present cross-sectional study, representative claims data sets for 2010 from Taiwan's National Health Insurance program, a health care system in which beneficiaries are not required to register with a family physician, were used to investigate the provision of health care to the population by family physicians. Among 919 206 beneficiaries with a total of 13 713 199 ambulatory visits, 49.1% had visited family physicians, 34.1% had visited internists, 24.3% had visited pediatricians, and 38.9% had visited otolaryngologists. Women (χ2(1) = 538, P <.001) and patients aged 65 and above (χ2(1) = 16 000, P <.001) had a higher proportion of visiting family physicians rather than visiting other specialties. The onion-shaped population pyramid with family medicine visits was compatible with the general population, and the proportion of visiting family physicians increased with increasing age. Among 112 289 patients with essential hypertension, 63 379 patients with diabetes mellitus, and 80 090 patients with hyperlipidemia, only 35.3%, 32.0%, and 31.1%, respectively, had visited family physicians. The age and sex distributions of these patients were illustrated with population pyramids for data visualization and direct comparisons. Taken together, the results of this study indicate that the utilization of family physicians in Taiwan and the effectiveness of their associated role in chronic disease management still have room for improvement.